ChemInform Abstract: Layered Perovskite Oxychloride Bi4NbO8Cl: A Stable Visible Light Responsive Photocatalyst for Water Splitting. Issue 26 (June 2016) - Fujito, Hironori; Kunioku, Hironobu; Kato, Daichi; Suzuki, Hajime; Higashi, Masanobu; Kageyama, Hiroshi; Abe, Ryu
Abstract: The title material is prepared by solid state reaction of a stoichiometric mixture of Bi2 O3, BiOCl, and Nb2 O5 (evacuated silica tube, 1173 K, 20 h) and characterized by powder XRD and UV/VIS diffuse reflectance spectroscopy.